Music and Popular Culture as Resources for the Study of the Transition to Democracy in the Basque Country - Mota Zurdo, David (Clio. History and History Teaching, 2018)
This article is a proposal of teaching unit for secondary school. Its goal is questioning the knowledgment that student body usually has of this tumultuous historical period and get them interested in this study throughout different and original information resources (fanzines, Music, etc.). Besides, the main goal of this article is setting out an inclusive narrative which flee from extreme positions, using a huge variety of educational means. This following proposal of teaching unit is a suggestive classroom practice.
Keywords: Spanish Democratic Transition; Democracy; Popular Culture; Educational Means; Music; Narrativess